Production of biodiesel from three indigenous feedstock: Optimization of process parameters and assessment of various fuel properties. Issue 3 (24th March 2017) - Chavan, Supriya B.; Yadav, Meena; Singh, Reena; Singh, Veena; Kumbhar, Rajendra R.; Sharma, Yogesh C.
Abstract : Biodiesel is a clean and sustainable fuel which has ability to replace diesel fuel used in power generation as well in transportation. This article explores Terminalia belerica Robx seed oil as an important bioresource for biodiesel synthesis. Extraction of terminalia oil from dried seeds and degumming of crude oil are also reported. Synthesis of biodiesel from waste vegetable oil and chicken fat oil as low‐cost biodiesel feedstocks has also been carried out. The oils are trans‐esterified using base homogeneous catalyst KOH and reaction variables were optimized for biodiesel synthesis. The biodiesel yields 89%, 89%, and 82% were obtained using feedstocks Terminalia oil, chicken fat oil, and waste vegetable oils, respectively, at individually optimized parameters such as molar ratio (methanol to oil), catalyst concentration, reaction temperature, reaction time, and agitation speed. The investigated fatty acid profile of feedstocks and different fuel properties of biodiesel were found to be as per ASTM D6751‐07b and EU 14214:2003 standards. This article deliberates the possibility of T. belerica seed oil, waste vegetable oil, and chicken fat oil as promising bioresources for biodiesel production considering the recycling and conversion of waste materials to value‐added products. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 788–795, 2017